Illness as a work of thought : a Foucauldian perspective on psychosomatics - Greco, Monica, 1966- (International library of sociology., 1998)
Illness as a Work of Thought is a practical application of Foucault's archaeological and genealogical methods of the study of illness and modernity. From medicine and psychiatry to psychology and the social sciences, Monica Greco explores what the history of these different disciplines contributes to what we understand by the term 'psychosomatics' and analyses how the study of psychosomatic illness can transform the way we think of illness, subjectivity and the ethics and politics of health